2016
DOI: 10.4238/gmr.15037976
|View full text |Cite
|
Sign up to set email alerts
|

Association between the WRAP53 gene rs2287499 C>G polymorphism and cancer risk: A meta-analysis

Abstract: ABSTRACT. The TP53 5'-untranslated region flanking the gene WRAP53 (also known as WDR79 and TCAB1) has been hypothesized to be associated with cancer risk due to its critical function in regulating p53 levels. In this review, we analyzed the association between the WRAP53 gene rs2287499 C>G polymorphism and risk of cancer using five case-control studies, comprising seven datasets. All analyses were performed using RevMan software. In the overall analysis, no significant association between rs2287499 and risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In this context, the common nonsynonymous SNP in codon 68 of the first coding exon of Wrap53 (rs2287499 c.202C>G) results in the amino acid change arginine (Arg 68 ) to glycine (Gly 68 ), which might affect protein function (33). In particular, the Wrap53 C>G SNP has been associated with primary tumor risk (33)(34)(35)(36)(37). However, the impact of this SNP on stroke remains unexplored.…”
Section: Wrap53 Rs2287499 C>g Snp Regulates Protein Nuclear Transloca...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the common nonsynonymous SNP in codon 68 of the first coding exon of Wrap53 (rs2287499 c.202C>G) results in the amino acid change arginine (Arg 68 ) to glycine (Gly 68 ), which might affect protein function (33). In particular, the Wrap53 C>G SNP has been associated with primary tumor risk (33)(34)(35)(36)(37). However, the impact of this SNP on stroke remains unexplored.…”
Section: Wrap53 Rs2287499 C>g Snp Regulates Protein Nuclear Transloca...mentioning
confidence: 99%
“…Inclusion criteria were patients admitted within the first 12 hours after the onset of symptoms (or from the start of sleep in those with symptoms upon awakening) who were previously independent for daily living activities. Patients receiving tissue reperfusion therapies (65), those included in clinical trials (33), and those showing severe systemic disease (28) were excluded. In addition, some patients (24) refused to participate in the study, and others (36) were lost during the follow-up.…”
Section: Patientsmentioning
confidence: 99%
“…In addition, Hube et al reported that alternative splicing of SRA1 could lead to the generation of coding and non-coding RNA isoforms in breast cancer cell lines [ 37 ]. Cao et al recently reported about the association between the WRAP53 gene rs2287499 C > G polymorphism and cancer risk [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Single Nucleotide Polymorphisms (SNPs) may alter gene regulation and structure and result in aberrant RNA or protein dysfunction. Although cancer-associated SNPs in determinant genes can increase the risk of cancer, as shown already for TP53 and WRAP53 in breast cancer susceptibility [18,19,20], it is necessary to define haplotype blocks to investigate the role of neighboring SNPs in cancer risk and calculate the linkage disequilibrium (LD) [21]. LD is the association between two nearby markers (e.g., SNPs), that result from common inheritance and are influenced by population size and mutation age.…”
Section: Introductionmentioning
confidence: 99%